Analysis Of Human Resource Quality And Organizational Culture On Employee Performance With Work Motivation As Mediating Variable In The West Medan District Office - Fatma Chairina; Muhammad Isa Indrawan; Elfitra Desy Surya (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is an important factor in determining the quality of public services in government agencies, including the West Medan Sub-District Office. Variations in employee performance indicate the need for an in-depth study of the factors that influence it. This study aims to analyze the influence of human resource quality and organizational culture on employee performance with work motivation as an intervening variable. The study uses a quantitative approach with a census method of all 60 civil servants (PNS) at the West Medan Sub-District Office as respondents. Data were collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results show that HR quality and organizational culture have a positive and significant effect on employee performance and work motivation. Work motivation was also found to have a positive and significant effect on employee performance. In addition, work motivation acted as an intervening variable that strengthened the effect of HR quality and organizational culture on employee performance. The coefficient of determination showed that the variables of HR quality and organizational culture were able to explain 44.3% of work motivation, while HR quality, organizational culture, and work motivation together explained 52.1% of employee performance. These findings confirm that improving employee performance at the West Medan Sub-District Office does not only depend on structural aspects such as HR quality and organizational culture, but is also greatly influenced by employee work motivation. Therefore, strengthening competencies, establishing a conducive organizational culture, and strategies to increase work motivation need to be prioritized in efforts to improve the quality of public services.